2020
DOI: 10.1111/1751-2980.12870
|View full text |Cite
|
Sign up to set email alerts
|

A randomized, multicenter and noninferiority study of amoxicillin plus berberine vs tetracycline plus furazolidone in quadruple therapy for Helicobacter pylori rescue treatment

Abstract: Objective Helicobacter pylori ( H. pylori ) infection is closely associated with gastric ulcers and gastric adenocarcinomas. We aimed to assess the efficacy and safety of a quadruple regimen with amoxicillin plus berberine vs tetracycline plus furazolidone in rescue therapy for H. pylori eradication. Methods We conducted a randomized, open‐label, multicenter, noninferiority trial. Patients with previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Furazolidone is widely used as an antibiotic in China for the eradication of H. pylori . Its efficacy and safety have also been well demonstrated ( 67 70 ). There were five furazolidone-resistant strains among our isolates, and the previously described mutations in the porD and oorD genes associated with furazolidone resistance were not found ( 46 ).…”
Section: Discussionmentioning
confidence: 97%
“…Furazolidone is widely used as an antibiotic in China for the eradication of H. pylori . Its efficacy and safety have also been well demonstrated ( 67 70 ). There were five furazolidone-resistant strains among our isolates, and the previously described mutations in the porD and oorD genes associated with furazolidone resistance were not found ( 46 ).…”
Section: Discussionmentioning
confidence: 97%
“…[ 21 , 22 ] According to a previous study by our group, tetracycline- and furazolidone-based quadruple therapy, which has an 85% eradication rate by PP analysis, is an ideal rescue strategy in patients with a previous eradication treatment failure. [ 23 ] Owing to adverse drug reactions [ 24 , 25 ] and difficulty with accessibility, the clinical use of tetracycline and furazolidone in the treatment of H. pylori has been severely limited. Our results demonstrated that HDDT consisting of esomeprazole plus amoxicillin achieved an eradication rate similar to that of bismuth quadruple therapy containing tetracycline and furazolidone and is an effective alternative for H. pylori rescue treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The average antibiotics resistance rates in Beijing were 0.3% (amoxicillin), 37.2% (clarithromycin), 1.7% (furazolidone), 63.9% (metronidazole), 1.2% (tetracycline), 50.3% (levofloxacin), and 61.9% (moxifloxacin), as in most parts of China (Gao et al, 2010; Hu et al, 2017). Although furazolidone and tetracycline are effective antibiotics, they have several side effects and are always not available (Chen et al, 2016; Zhang et al, 2014, 2020; Zhuge et al, 2018). China's food and drug agency announced in 2018 (no.…”
Section: Discussionmentioning
confidence: 99%